Yes please - Poehler, Amy, 1971- (New York, NY : Dey St., an imprint of HarperCollinsPublishers, 2014)
The actress best known for her work on "Parks and Recreation" and "Saturday Night Live" reveals personal stories and offers her humorous take on such topics as love, friendship, parenthood, and her relationship with Tina Fey.
Keywords: Poehler, Amy, -- 1971-; Parks and recreation (Television program); Saturday night live (Television program); Television actors and actresses -- United States -- Biography; Women comedians -- United States -- Biography; Actors -- United States -- Biography